BIVALVE ZONATION IN PERMIAN DEPOSITS OF NORTHEASTERN ASIA - Byakov A.S. (My University, 2000)
Detailed stratigraphical and paleontological investigations of many sections in the Kolyma and Omolon river basins and the Okhotsk area resulted in the elaboration of biostratigraphic bivalve zonation of Permian deposits in northeastern Asia (excluding the Koryak Upland). The zonal scheme consists of 11 zones. In addition, two auxiliary units (beds with fauna) were recognized in the Gizhiga Horizon of the Upper Permian. All zones are characterized by zonal bivalve assemblages, and are by nature biostratigraphic zones. The zonation is based on stages in the phylogenetic evolution of inoceram-like bivalves, which are least dependent on facies factors and usually occur in abundance. Possible correlations of the established zonation with those in the Verkhoyansk and Baikal regions, Novaya Zemlya, Taimyr, northern Russian platform, North America, Australia, New Zealand, and other regions are demonstrated.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская